Emergency Care Capabilities in North East Haiti: A Cross-sectional Observational Study. Issue 6 (21st October 2015) - De Wulf, Annelies; Aluisio, Adam R.; Muhlfelder, Dana; Bloem, Christina
Abstract: Introduction: The North East Department is a resource-limited region of Haiti. Health care is provided by hospitals and community clinics, with no formal Emergency Medical System and undefined emergency services. As a paucity of information exists on available emergency services in the North East Department of Haiti, the objective of this study was to assess systematically the existing emergency care resources in the region. Methods: This cross-sectional observational study was carried out at all Ministry of Public Health and Population (MSPP)-affiliated hospitals in the North East Department and all clinics within the Fort Liberté district. A modified version of the World Health Organization (WHO) Tool for Situational Analysis to Assess Emergency and Essential Surgical Care and Generic Essential Emergency Equipment Lists were completed for each facility. Results: Three MSPP hospitals and five clinics were assessed. Among hospitals, all had a designated emergency ward with 24 hour staffing by a medical doctor. All hospitals had electricity with backup generators and access to running water; however, none had potable water. All hospitals had x-ray and ultrasound capabilities. No computed tomography scanners existed in the region. Invasive airway equipment and associated medications were not present consistently in the hospitals' emergency care areas, but they were available in the operating rooms. Pulse oximetry was unavailable uniformly. One hospital had intermittently functioning defibrillation equipment, and two hospitals had epinephrine. Basic supplies for managing obstetrical and traumatic emergencies were available at all hospitals. Surgical services were accessible at two hospitals. No critical care services were available in the region. Clinics varied widely in terms of equipment availability. They uniformly had limited emergency medical equipment. The clinics also had inconsistent access to basic assessment tools (sphygmomanometers 20% and stethoscopes 60%). A protocol for transferring patients requiring a higher level of care was present in most (80%) clinics and one of the hospitals. However, no facility had a written protocol for transferring patients to other facilities. One hospital reported intermittent access to an ambulance for transfers. Conclusions: Deficits in the supply of emergency equipment and limited protocols for inter-facility transfers exist in North East Department of Haiti. These essential areas represent appropriate targets for interventions aimed at improving access to emergency care within the North East region of Haiti. A De Wulf, AR Aluisio, D Muhlfelder, C Bloem .Emergency care capabilities in North East Haiti: a cross-sectional observational study .Prehosp Disaster Med .2015 ;30 (6 ):553 –559 .